2023
DOI: 10.3389/ftox.2023.1178482
|View full text |Cite
|
Sign up to set email alerts
|

Daphnia as a model organism to probe biological responses to nanomaterials—from individual to population effects via adverse outcome pathways

Abstract: The importance of the cladoceran Daphnia as a model organism for ecotoxicity testing has been well-established since the 1980s. Daphnia have been increasingly used in standardised testing of chemicals as they are well characterised and show sensitivity to pollutants, making them an essential indicator species for environmental stress. The mapping of the genomes of D. pulex in 2012 and D. magna in 2017 further consolidated their utility for ecotoxicity testing, including demonstrating the responsiveness of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 196 publications
0
2
0
Order By: Relevance
“…Their results are instrumental in advancing our understanding of the potential risks and impacts of nanomaterials on aquatic organisms. 32,[76][77][78] The growing interest in using NFs of agrochemicals led us to assess the toxicity of different nanomaterials, polymeric, and lipid-based nanomaterials loading tebuconazole on the survival of D. magna.…”
Section: Toxicity For Daphnia Magnamentioning
confidence: 99%
“…Their results are instrumental in advancing our understanding of the potential risks and impacts of nanomaterials on aquatic organisms. 32,[76][77][78] The growing interest in using NFs of agrochemicals led us to assess the toxicity of different nanomaterials, polymeric, and lipid-based nanomaterials loading tebuconazole on the survival of D. magna.…”
Section: Toxicity For Daphnia Magnamentioning
confidence: 99%
“…AgNPs have been documented to generate oxidative damage and tissue damage to fish [23,24], which can impair the survival and growth of invertebrates such as D. magna, as well as other aquatic life, including algae [25][26][27]. However, it is worth noting that in the available literature, studies on the ecotoxicological impact of AgNPs have shown inconsistent results [28][29][30][31][32], where the EC 50 values of AgNPs vary significantly across studies due to the inconsistency of experimental designs across laboratories. Therefore, this makes the evaluation of the impact of AgNPs in the ecotoxicological context very difficult.…”
Section: Introductionmentioning
confidence: 99%